Produtividade e qualidade de frutos da cultivar de videira 'BRS Magna' em função dos sistemas de podas e dos porta-enxertos em Pato Branco, Paraná - Goulart, Vanessa Mayra de Assis (2025)
In the Southwest region of Paraná, viticulture has emerged as an activity of significant relevance. The vineyards established in this region are mostly part of family farming systems and represent an important source of income diversification, with the production of various products such as wine, vinegar, juice, sweets, and jams. With the growing consumption of grape juice and the recent introduction of the 'BRS Magna' variety, intended for juice production and currently being tested in the Southwest region, it has become necessary to define the most efficient pruning system in combination with rootstocks for this cultivar.Therefore, this study aimed to evaluate the impact of different pruning systems and rootstocks on the yield and fruit quality of the 'BRS Magna' grapevine. The experiment was conducted in Pato Branco (PR) following a randomized block design in a split-plot scheme with four replications, arranged in a 4×2 factorial. Factor A consisted of the rootstocks: ‘1103 Paulsen’, ‘IAC 572 Jales’, ‘IAC 766 Campinas’ and ‘IAC 313 Tropical’; and Factor B, the pruning systems: spur-pruned cordon and double Guyot.No significant effects of the rootstocks, pruning systems or their interaction were observed on yield components or grape quality variables of the ‘BRS Magna’ cultivar in the 2023 and 2024 harvests. Therefore, for this cultivar and under the conditions of this experiment, the spur-pruned cordon system is recommended due to its ease of implementation.